Reading girls reading pleasure : reading, adolescence and femininity - Armstrong, Nancy Jane (Curtin University, 2009)
This thesis is concerned with the reading girl and the potential pleasures and transgressions she experiences through popular fiction. Throughout modernity, the western bourgeois girl has been directed towards texts that both validate proper, and caution against improper, forms of femininity. This practice continues within the institutions of family and education as well as through the public library system and commercial booksellers. Although the contemporary girl is subjected to feminism, culture continues to insist on her domestic role. The notion of identification is central to societal fears about the material that finds its way into the hands of reading girls. Because the reading girl can align herself imaginatively with characters, commentators worry that she might absorb passivity from passive characters, wanton habits from wanton characters, or murderous habits from murderous characters. Reading theory tends to reinforce these fears through a particularly disparaging assessment of popular fictions. The girl‘s identifications with characters in popular fiction continue to worry her familial, educational, psychological and moral guardians.Using a methodology based on the psychoanalytic theories of Jacques Lacan, I consider the girl reader as a subject split between her unconscious and the identity she cobbles together through identifications with embodied and representational others. Because of this foundational split, she can never fully articulate reading pleasures and their effects can never be calculated with consequence. Reading participates in the girl‘s struggle to achieve the precarious feminine position, and provides her with pleasures along the way. To demonstrate some of the pleasures available to the girl, I undertake readings of texts associated with adolescence and femininity. I examine young adult fiction that is directed at the adolescent reader to expose the pleasures that lie beneath the injunction to adopt a heteronormative adult identity. From books addressing the girl, I move to melodramatic and sensational adult fictions located in the domestic. In these fictions, the girl is stifled and distorted because she is captive to her family and cannot escape to establish the direction of her desire and seek the recognition of the social Other. Finally, I look at texts marked by violence. Taking one fictional text from the horror genre, and one non-fictional true crime text, I explore the unspeakable pleasures of reading about blood and death.In these readings, I investigate both conservative and transgressive pleasures. These pleasures co-exist in all of the fictions explored in this thesis. All reading tends towards the cautionary, and the book cannot corrupt the normally constituted reading girl. Through identifying with characters, she can build up a repertoire of feminine masks and develop an awareness of the precarious position of womanliness. In the end, I argue, the adolescent reading girl cannot be determined or totalised despite the best efforts of the book and its commentators.